Simulating Nanomaterial Transformation in Cascaded Biological Compartments to Enhance the Physiological Relevance of In Vitro Dosing Regimes: Optional or Required?. Issue 15 (21st January 2021) - Llewellyn, Samantha V.; Kämpfer, Angela; Keller, Johannes G.; Vilsmeier, Klaus; Büttner, Veronika; Ag Seleci, Didem; Schins, Roel P. F.; Doak, Shareen H.; Wohlleben, Wendel
Abstract: Would an engineered nanomaterial (ENM) still have the same identity once it reaches a secondary target tissue after a journey through several physiological compartments? Probably not. Does it matter? ENM pre‐treatments may enhance the physiological relevance of in vitro testing via controlled transformation of the ENM identity. The implications of material transformation upon reactivity, cytotoxicity, inflammatory, and genotoxic potential of Ag and SiO2 ENM on advanced gastro‐intestinal tract cell cultures and 3D liver spheroids are demonstrated. Pre‐treatments are recommended for certain ENM only. Abstract : This article investigates the physicochemical changes exhibited by engineered nanomaterials (ENMs) treated with presimulants representing inhalation and oral exposure routes, and the subsequent effects of such ENM biotransformation upon primary and secondary organ systems. To evaluate this, ENM characterization is undertaken whilst cytotoxicity, (pro‐)inflammatory response, and genotoxicity are assessed using in vitro models.